Konstruksi Teologis dalam Sistem Pemujaan Śiwa-Buddha di Pura Dasar Buana Amerta Jati Śiwa Buda Desa Tajun - Kariarta, I Wayan (Jurnal Penelitian Agama Hindu, 2025)
Pura Dasar Buana Amerta Jati Śiwa Buda is a temple built upon the theological values of Śiva and Buddha. The effort to actualize these Śiva-Buddha theological values serves as a concrete manifestation of mahayu-hayuning bhuana (preserving the harmony of nature). The existence of the Śiva-Buddha concept in Tajun Village has raised questions from various parties regarding the theological construction present in the Bali Aga region. This study uses observation, interviews, and documentation studies as data collection methods. A qualitative descriptive method is employed to present the research findings. Based on the results, it was found that Sang Hyang Śiva and Sang Hyang Buddha are regarded as a single entity (ya Buddha ya Śiva) by the people of Tajun Village. Sang Hyang Śiva is worshipped through a pelinggih prasada, while Sang Hyang Buddha is venerated through a pelinggih stupa. The Śiva-Buddha syncretism in Pura Dasar Buana Amerta Jati Śiwa Buda has shaped the religious patterns and theological understanding of the Tajun community. A society that once viewed rwa-bhineda (duality) as something dichotomous now perceives it as paradoxical. Regardless of the chosen path whether through Śiva or Buddha, it ultimately leads to the same goal. This understanding is essentially aligned with the concept of Saguna Brahman found in Smriti texts. Engaging actively in worship of the Divine does not imply neglecting the social dimension of life, as life must remain balanced between the profane and the sacred. Furthermore, social solidarity must be built upon the principle of tatwamasi in order to be free from personal interest and to offer solutions to human problems. The theological values of Śiva-Buddha that have thus far succeeded in maintaining harmony among religious communities should continue to be preserved at all times.